Predictors of Postpartum Depression: The Role of Emotion Regulation, Maternal Self-Confidence, and Marital Satisfaction on Postpartum Depression - Dinni, Siti Muthia; Ardiyanti, difa (Faculty of Psychology, Universitas Gadjah Mada, 2020)
Postpartum Depression (PPD) is a serious mother’s mental health problem that may endanger the safety of mother and her child. This study aimed to identify whether emotion regulation, maternal self-confidence, and marital satisfaction could be a significant predictor of PPD. The participants of this study were 100 women who gave birth in the past 2-24 weeks. Research instruments presented via online platform, comprised of: ASIPP (Alat Asesmen Ibu Postpartum/Postpartum Maternal Assessment Tool containing the Emotion Regulation Scale, the Maternal Self-Confidence Scale, and the Marital Satisfaction Scale) and the early detection scale for postpartum depression. Regression analysis showed that only maternal self-confidence and emotional regulation were proven significant in simultaneously predicting PPD, while marital satisfaction was not proven to significantly predict PPD either partially or simultaneously. This finding suggested that psychological prevention programs for postpartum mothers were better focused on encouraging maternal self-confidence and emotion regulation ability of the mothers.